2013
DOI: 10.2355/isijinternational.53.1286
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Dislocations and Crystallographic Texture during Martensitic Reversion into Austenite

Abstract: KEY WORDS: austenite; martensitic reversion; reversible martensitic transformations; crystallographic memory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…9. Austenite islands preferentially nucleate at triple junctions, intersections of lath and high-angle grain boundaries, and at PAGBs, as has been observed for Fe-Mn [37,38] and Fe-C [39][40][41]. Table 2 displays absolute grain boundary concentrations and excess values of Mn, C, B and P for different tempering states for both the model alloys Mn9 and Mn9+B.…”
Section: Apt Resultsmentioning
confidence: 68%
“…9. Austenite islands preferentially nucleate at triple junctions, intersections of lath and high-angle grain boundaries, and at PAGBs, as has been observed for Fe-Mn [37,38] and Fe-C [39][40][41]. Table 2 displays absolute grain boundary concentrations and excess values of Mn, C, B and P for different tempering states for both the model alloys Mn9 and Mn9+B.…”
Section: Apt Resultsmentioning
confidence: 68%
“…It is known that the reversible transformation from martensite to austenite (martensitic reversion) occurs in maraging steel owing to its high Ni content. [1][2][3][4] Previously, 5) the authors of the current study directly observed an austenitic structure formed by martensitic reversion (martensitically reversed austenite) in 18%Ni-C (% = wt.%) steel. It was reported that after reheating the sample to a temperature above the martensitic austenite-start temperature, As, all martensite laths originally formed via an fcc→bcc martensitic transformation reverse into new austenite during the bcc→fcc martensitic reversion, thus returning to an original austenitic structure with the same crystallographic orientation.…”
mentioning
confidence: 76%
“…4(a-2)-4(d-2)) indicate that the lath martensitic structure is characterized by high angle block and packet boundaries and that there is no significant difference in the density of these boundaries among specimens. To reveal the occurrence of the displacive reversion, we must focus not on block and packet boundaries but on the prior austenite grain boundaries; this is because while the original austenite grain boundaries remained in displacive reversion, 3,5) new austenite grains were formed through nucleation and growth in diffusive reversion. In other words, the austenite grain size does not change during displacive transformations.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…Another group of interfaces in the lath martensitic microstructure are prior austenite grain boundaries [11,49]. In contrast to packet, block and sub-block boundaries, the character of prior austenite grain boundaries is not determined by the austenitemartensite orientation relationship.…”
Section: Discussionmentioning
confidence: 99%